The Influence of Social Class on The English Spoken By Students In Selected Secondary Schools Of Mpondwe Lhubiriha Town Council Kasese District. - Masereka, Gilson (Kabale University, 2024)
The study aimed to examine the influence of social class on English spoken by students in selected secondary schools in Mpondwe Lhubiriha Town Council Kasese district. The study was guided by the following objectives; to explain the negative influence of social class on the English spoken by students in Mpondwe Lhubiriha Town Council Kasese district; to explain the positive influence of social class on the English spoken by students in Mpondwe Lhubiriha Town Council Kasese district; to devise measures towards improving English spoken by students in Mpondwe Lhubiriha Town Council Kasese district.